A manufacturing perspective on graphene dispersions. Issue 5 (October 2015) - Johnson, David W.; Dobson, Ben P.; Coleman, Karl S.
Abstract: Harnessing the exceptional physical properties of graphene often requires its dispersion into aqueous or organic media. Dispersion must be achieved at a concentration and stability appropriate to the final application. However, the strong interaction between graphene sheets means it disperses poorly in all but a few high boiling organic solvents. This review presents an overview of graphene dispersion applications and a discussion of dispersion strategies: in particular the effect of shear, solvent and chemical modification on the dispersion of graphene (including graphene oxide and reduced graphene oxide). These techniques are discussed in the context of manufacturing and commercialisation.